Analisis Potensi Energi Surya di Area ITSNU Pekalongan - Abdul Hakim Prima Yuniarto; Yuni Lestiyanti; Alfin Najib; Indanah (Jurnal Pendidikan Fisika dan Sains (JPFS), 2025)
Pekalongan, there are many industries, especially the clothing industry, such as batik, sarongs, jeans, etc. Apart from that, in Pekalongan, there are also several universities with high-rise buildings. This large population results in high levels of electrical energy consumption. So far, the supply of electrical energy is still dominated by fossil energy, where fossil energy reserves are increasingly depleting and can result in environmental pollution. One of the renewable energies is solar energy. Solar energy can be utilized to become a solar power plant, it can be applied to buildings. Therefore, this research aims to analyze the potential of solar energy in the ITSNU Pekalongan area. An analysis of solar energy potential can be done by calculating the roof area using GIS. Based on research results, the largest global irradiation value is in a north direction of 4880 kWh/m2/day. Meanwhile, the smallest global irradiation value is at a south direction of 4198 kWh/m2/day. The number of solar panels that can be installed on the roof is 1262 units. These solar panels have the potential to produce peak power of 378,721 Wp or 378,721 kWp daily. This peak power can be converted into energy of 1,893,606 Wh, or 1893,606 kWh, daily.